Global Solvability of Linear Differential Operators with Multiple Characteristics (Journal of Partial Differential Equations, 2020)
In this paper, we first introduce the irreducible unitary representation of nilpotent Lie groups, then by using the irreducible unitary representation we construct a fundamental solution to a class of left invariant differential operators and thus obtain the global solvability of this kind of operators.
Keywords: Irreducible unitary representation; left invariant differential operators; global solvability